Experimental Investigation of the Effects of Machining Parameters on the Performance of Form-Cutting Tools Manufactured by Wire Electrical Discharge Machining (WEDM) and Grinding Processes - Amir Alinaghizadeh; Mohammadjafar Hadad; Bahman Azarhoushang (Micromachines, 2023)
In this research, a comparison between two methods of grinding and WEDM and the chip formation of each form tool was studied through a set of designs of experiments. A multi-functional form tool with different cutting-edge shapes was designed to compare different production methods, and a grinding machine and a five-axis wire-cutting machine were made. The form tools by the wire cutting method were made with three different machining states, rough, semi-finish, and finish. The results of the experimental test showed that the chip formation of the finished surface of the wire cut tool was close to the ground tools. Additionally, the tool life in wear generation was assessed, revealing that the tool generated through the wire-cutting method with three passes exhibited superior performance compared to alternative approaches. Furthermore, employing the wire-cutting technique with high surface finishing yielded optimal outcomes for producing form-cutting tools featuring complex profiles.